NEW APPROACH TO SEPARATE AND DATE SMALL SPORES AND POLLEN FROM LAKE SEDIMENTS IN SEMI-ARID CLIMATES. Issue 5 (7th October 2022) - Steinhoff, Christoph; Pickarski, Nadine; Litt, Thomas; Hajdas, Irka; Welte, Caroline; Wurst, Peter; Kühne, David; Dolf, Andreas; Germer, Maximilian; Kallmeyer, Jens
ABSTRACT: The dating of pollen grains is emerging as the method of choice for lacustrine climate archives that contain few datable macrofossils. Due to the need for high-purity pollen concentrates, new methods are constantly being developed to precisely separate pollen grains. Flow cytometry represents a promising alternative to conventional approaches, enabling the identification of pollen grains through fluorescence and rapid separation for radiocarbon analysis using accelerator mass spectrometry, which has so far been limited to sediments with a high proportion of conifer pollen. We present a revised method for processing large sediment samples, resulting in high-purity pollen and spore concentrates. Using this approach small- to medium-sized pollen and bryophyte spores were isolated from Lake Van sediment samples (Eastern Anatolia, Turkey) in sufficient purity for radiocarbon dating. However, a systematic age discrepancy between pollen and bryophyte spore concentrates was noted. By adapting the chemical and cytometric methods, pure pollen concentrates can be created for sediments with low organic content enabling age determination of climate archives with a low proportion of large pollen or low pollen concentration.